A minority of T cells recognizing tumor-associated antigens presented in self-HLA can provoke antitumor reactivity - Roex, Marthe C. J.; Hageman, Lois; Veld, Sabrina A. J.; Van Egmond, Esther; Hoogstraten, Conny; Stemberger, Christian; Germeroth, Lothar; Einsele, Hermann; Falkenburg, J. H. Frederik; Jedema, Inge (Blood, 2020)
Tumor-associated antigens (TAAs) are monomorphic self-antigens that are proposed as targets for immunotherapeutic approaches to treat malignancies. We investigated whether T cells with sufficient avidity to recognize naturally overexpressed self-antigens in the context of self-HLA can be found in the T-cell repertoire of healthy donors. Minor histocompatibility antigen (MiHA)-specific T cells were used as a model, as the influence of thymic selection on the T-cell repertoire directed against MiHA can be studied in both self (MiHApos donors) and non-self (MiHAneg donors) backgrounds. T-cell clones directed against the HLA*02:01-restricted MiHA HA-1H were isolated from HA-1Hneg/HLA-A*02:01pos and HA-1Hpos/HLA-A*02:01pos donors. Of the 16 unique HA-1H-specific T-cell clones, five T-cell clones derived from HA-1Hneg/HLA-A*02:01pos donors and one T-cell clone derived from an HA-1Hpos/HLA-A*02:01pos donor showed reactivity against HA-1Hpos target cells. In addition, in total, 663 T-cell clones (containing at least 91 unique clones expressing different T-cell receptors) directed against HLA*02:01-restricted peptides of TAA WT1-RMF, RHAMM-ILS, proteinase-3-VLQ, PRAME-VLD, and NY-eso-1-SLL were isolated from HLA-A*02:01pos donors. Only 3 PRAME-VLD-specific and one NY-eso-1-SLL-specific T-cell clone provoked interferon-g production and/or cytolysis upon stimulation with HLA-A*02:01pos malignant cell lines (but not primary malignant samples) naturally overexpressing the TAA. These results show that self-HLA-restricted T cells specific for self-antigens such as MiHA in MiHApos donors and TAAs are present in peripheral blood of healthy individuals. However, clinical efficacy would require highly effective in vivo priming by peptide vaccination in the presence of proper adjuvants or in vitro expansion of the low numbers of self-antigen-specific T cells of sufficient avidity to recognize endogenously processed antigen.
CRIS-Team Scopus Importer:2023-03-23